Importance of antiresorptive therapies for patients with bone metastases from solid tumors - Talreja DB (Cancer Management and Research, 2012)
Draupadi B TalrejaDepartment of Medicine, David Geffen School of Medicine at UCLA and Northridge Hospital Medical Center, Northridge, CA, USAAbstract: Patients with bone metastases are at risk of skeletal-related events such as pathologic fractures, spinal cord compression, the need for orthopedic surgery to bone, and palliative radiotherapy for severe bone pain. Antiresorptive therapies have demonstrated efficacy for reducing the risk of skeletal-related events and ameliorating bone pain. Despite the well documented clinical benefits of antiresorptive therapies, patient benefits can be limited or compromised by nonadherence with scheduled therapy. Potential reasons for poor compliance include lack of understanding of how antiresorptive therapies work, neglecting the importance of bone health in maintaining quality of life, and being unaware of the potentially debilitating effects of skeletal-related events caused by bone metastases. Indeed, patients may stop therapy after bone pain subsides or discontinue due to generally mild and usually manageable adverse events, leaving them at an increased risk of developing skeletal-related events. In addition, the cost of antiresorptive therapy can be a concern for many patients with cancer. Medical care for patients with cancer requires a coordinated effort between primary care physicians and oncologists. Patients' medical care teams can be leveraged to help educate them about the importance of adherence to antiresorptive therapy when cancer has metastasized to bone. Because primary care physicians generally have more contact with their patients than oncologists, they are in a unique position to understand patient perceptions and habits that may lead to noncompliance and to help educate patients about the benefits and risks of various antiresorptive therapies in the advanced cancer setting. Therefore, primary care physicians need to be aware of various mechanistic and clinical considerations regarding antiresorptive treatment options.Keywords: antiresorptive therapy, bisphosphonates, bone metastases, cancer, denosumab, zoledronic acid